2013
DOI: 10.5005/jp-journals-10023-1065
|View full text |Cite
|
Sign up to set email alerts
|

Urbach-Wiethe Disease: A Rare Cause of Hoarseness of Voice

Abstract: Urbach-Wiethe disease is a rare, autosomal recessive disorder, characterized by infiltration of periodic acid-Schiff positive hyaline material into the skin, oral cavity, larynx and internal organs. The clinical manifestations include hoarseness of voice, beaded papules along the eyelid margins, skin scarring and an inability to protrude the enlarged and thickened tongue. Laryngeal involvement is typical and causes hoarseness of voice. In this paper, we present a case of a middle-aged female with clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although many autopsy studies have found that LP can be defined as a generalized disorder with microscopic hyaline deposition in practically every organ, the symptoms related to other visceral organs have not been clarified yet. [32,33] Hoarseness has been identified as the first symptom of LP. Moreover, it was also the first finding in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many autopsy studies have found that LP can be defined as a generalized disorder with microscopic hyaline deposition in practically every organ, the symptoms related to other visceral organs have not been clarified yet. [32,33] Hoarseness has been identified as the first symptom of LP. Moreover, it was also the first finding in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Skin lesions are generally seen as nodules on the face and lips (at earlier stages), and they then become hyperkeratotic. [33,34] In some patients, symptoms may be observed since birth. Since voice hoarseness occurs in neonatal period, it is one of the three entities that should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes thickening of the vocal cords and adjacent tissues is also seen. Many patients are unable to open full mouth and laryngoscopy is not possible 9 . In present case report there was also difficulty in opening the mouth and intubation was very difficult that why we used only 5.5 mm ETT for intubation.…”
Section: Discussionmentioning
confidence: 99%